2018
DOI: 10.5935/0103-507x.20180023
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the neuropsychomotor development in the first year of life of premature infants with and without bronchopulmonary dysplasia

Abstract: ObjectiveTo compare the neuropsychomotor development in the first year of life of premature infants with and without bronchopulmonary dysplasia.MethodsA cross-sectional retrospective study was conducted between January 1, 2014, and December 30, 2015, with premature infants weighing < 1,500g at birth and diagnosed with bronchopulmonary dysplasia at the corrected ages of 6 and 9 months, assessed using the DENVER II Developmental Screening Test. Quantitative variables were described as the means, medians and stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…It is noted that no associations were found between birth weight and neuro-psychomotor development, 12 which showed that 8% of preterm children had an average birth weight of 3,276 kg, with the lowest weight being 460 g and the highest weight, 4,700 g, with no significant relationship between gestational age and birth weight and the result of neuro-psychomotor development. However, it was found in a study, 7 that low birth weight can increase the risk of developmental delay. It is also emphasized that other variables associated with prematurity have been shown to be determinants for changes in neuro-psychomotor development.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…It is noted that no associations were found between birth weight and neuro-psychomotor development, 12 which showed that 8% of preterm children had an average birth weight of 3,276 kg, with the lowest weight being 460 g and the highest weight, 4,700 g, with no significant relationship between gestational age and birth weight and the result of neuro-psychomotor development. However, it was found in a study, 7 that low birth weight can increase the risk of developmental delay. It is also emphasized that other variables associated with prematurity have been shown to be determinants for changes in neuro-psychomotor development.…”
Section: Resultsmentioning
confidence: 96%
“…6 It is revealed, for the variables of the responsible person's gender and age group, that no statistical significance was evidenced, corroborating other findings in the literature, such as a study carried out in the reference university hospital of the State of Minas Gerais, in 2015, in which they were evaluated 79 medical records of premature children aged six to 12 months, submitted to the Denver II test, which obtained the same result as this study, not finding an association between child development and these variables. 7 It is understood that several studies, point to the influence of biological, nutritional, socioeconomic, family factors and the availability of access to services as contributors to neuropsychomotor development, reinforcing its multifactorial potential. 8 In a study carried out in Belém (PA), 2 in which 318 children, of both sexes, from 36 to 48 months of age were screened, that there was a significant association between parents' schooling and child development, corroborating this study, since, as a result of the higher education level of parents, the probability of having a reasonably better occupation is greater and, as a result, there may be a more satisfactory DISCUSSION remuneration, which ensures better living conditions, access to health, nutrition, among other factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediate identi cation of high-risk newborns may reduce perinatal morbidity and mortality [3,4]. If the AS is low and comorbidity such as bronchopulmonary dysplasia is present, there is an increased chance of delayed neuropsychomotor development in the premature neonate weighing less than 1500 g. This shows that the scale has great relevance in the prior identi cation of diseases and conditions associated with the neurological system [5].…”
Section: Introductionmentioning
confidence: 99%
“…The literature shows that preterm infants have worse performance in language tests and skills such as gross motor, fine-adaptive motor and personal-social compared to term children (1)(2)(3) . On the other hand, some studies report that the language impairment not as a condition related to prematurity but related to factors such as gestational age (4)(5)(6)(7) and birth weight (4)(5)(6)(7)(8) . These last two variables are believed to negatively influencing the development of pre-linguistic skills and language outcomes in preterm children (7) .…”
Section: Introductionmentioning
confidence: 99%